Penentu Respon Petani Terhadap Budidaya Dan Pemanfaatan Sorgum: Studi Kasus di Desa Kawalelo Kecamatan Demon Pagong Kabupaten Flores Timur, NTT - Goran, Mathilda Bura; Sinu, Ignatius; R. Pellokila, Marthen (Journal of Agricultural Socio-Economics (JASE), 2021)
Sorghum is an important alternative food commodity for some rural communities in East Nusa Tenggata (NTT). This research is to find out the determinants of farmers' responses to the cultivation and utilization of sorghum in the research area. This study involved 30 respondents in sorghum cultivation and 30 respondents from non-sorghum cultivation which were found intentionally. Using survey methods to obtain data. Data were analyzed using the logistic regression model. The results of the study found that the factors that significantly influenced the cultivation and utilization of sorghum were non-formal education factors and the number of family dependents. This finding indicates that sorghum is used as an alternative food if staple food is reduced (entering a famine). The public needs to be educated and advocated that sorghum is not only used as an alternative food commodity in case of food shortages, but sorghum has high nutritional value and is easy to cultivate. Government intervention and the role of the community need to be increased in educating and advocating for farmers.